2021
DOI: 10.3390/antiox10050755
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Coenzyme Q10 in Cardiovascular Diseases

Abstract: CoQ10 is an endogenous antioxidant produced in all cells that plays an essential role in energy metabolism and antioxidant protection. CoQ10 distribution is not uniform among different organs, and the highest concentration is observed in the heart, though its levels decrease with age. Advanced age is the major risk factor for cardiovascular disease and endothelial dysfunction triggered by oxidative stress that impairs mitochondrial bioenergetic and reduces NO bioavailability, thus affecting vasodilatation. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 111 publications
0
28
0
Order By: Relevance
“…Numerous studies indicate a significant role of its deficiency in the pathogenesis of HF. Therefore, several clinical trials have been conducted to assess the effectiveness of coenzyme Q10 supplementation in patients with HF, with very good results [ 10 , 11 ].…”
Section: Heart Failure—a Civilization Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies indicate a significant role of its deficiency in the pathogenesis of HF. Therefore, several clinical trials have been conducted to assess the effectiveness of coenzyme Q10 supplementation in patients with HF, with very good results [ 10 , 11 ].…”
Section: Heart Failure—a Civilization Diseasementioning
confidence: 99%
“…From the point of view of cardiovascular health, it is worth mentioning that coenzyme Q10 is a natural antioxidant, which is characterized by stronger antioxidant properties in relation to low density lipoproteins (LDL) than β-carotene or α-tocopherol [ 10 , 15 , 17 ]. Moreover, coenzyme Q10 takes part in the recycling of antioxidants such as vitamin C or vitamin E [ 13 ].…”
Section: Coenzyme Q10—brief Biochemical Overviewmentioning
confidence: 99%
“…Most of the CoQ10 related studies we found in our organ-specific research concerned the heart. This can probably be explained by the fact that people suffering from heart diseases show a depletion of CoQ10 [ 73 ], emphasizing its importance in heart physiology (see, also, Reference [ 74 ]). A particularly interesting aspect of CoQ10 in relation to cardiovascular health is that CoQ10 in and of itself has the potential to provide preventive support in heart failure, a fact that eventually makes the need for heart transplants (and, thus, fighting IRI) obsolete in the first place.…”
Section: Coenzyme Q10mentioning
confidence: 99%
“…These include cellular calcium loading, endothelium cell swelling, impaired vascular relaxation, and the action of oxygen radicals [35]. In clinical situations, the outcomes for acute coronary syndrome patients who are suffering from I/R are influenced by many unpredictable events, such as myocardial stunning, coronary vascular spasms, or lethal arrhythmia [36]. The molecular signaling changes of myocardial I/R injury which are needed to be further studied.…”
Section: Study Limitation and Future Directionsmentioning
confidence: 99%